(untitled) (American Journal of Islam and Society, 1997)
I am hesitant to speak on the role of ijtihiid in an Islamic capital market, because this topic requires understanding two important but difficult areas whose primary sources are in different languages. The first area is ijtihiid which is connected withfiqh issues; the majority of its sources are in Arabic. The second area is economics which is connected with the analysis of capital markets; the majority of its sources are in European languages. Linking ethics and economics is necessary but difficult. Necessary, because every economic choice has a spiritual dimension. Difficult, because secular economics severs the link, by reducing values to tastes and arguing that different ethical values do not change the method of choice. Therefore, properly linking ijtihiid and economics is a difficult task, requiring determined effort to refute the secular separation of ethics and economics. I spent over 100 hours thinking, reading, and analyzing the essential points of both until I could establish common ground between them. Ijtihad is of central importance in usul al-fiqh, and concerns the method of implementing the spirit of the sacred texts in any environment. Since the third century A.H., ijtihd has been the main theme of dialog between the different schools of fiqh. To this day scholars debate the issue. Economics is an important science in our time, influencing several other sciences. Since the capital market is a significant topic in economics, it is important to understand the strengths and weaknesses of the neoclassical analysis of capital markets’ in developing an Islamic capital market. We must also understand the history of economic thought, how capital markets became an important part of it, and why many ...